2018
DOI: 10.1186/s12014-018-9196-y
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive proteome analysis of nasal lavage samples after controlled exposure to welding nanoparticles shows an induced acute phase and a nuclear receptor, LXR/RXR, activation that influence the status of the extracellular matrix

Abstract: Background Epidemiological studies have shown that many welders experience respiratory symptoms. During the welding process a large number of airborne nanosized particles are generated, which might be inhaled and deposited in the respiratory tract. Knowledge of the underlying mechanisms behind observed symptoms is still partly lacking, although inflammation is suggested to play a central role. The aim of this study was to investigate the effects of welding fume particle exposure on the proteome expression leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…The levels of both nanoparticles (average size in general between 50 and 100 nm, as measured using the Nanotracer) and slightly larger particles (0.3 μm measured using the Lighthouse) were constantly much higher in the welding facility compared with the AM facility. High levels of nanoparticles in welding facilities are in line with what we found in the pilot study [7] and what is known from recent studies focusing on welding [15]. This may depend on the fact that in the welding facility, there are a wide array of different processes including welding, metal cutting, and combustion engines that may contribute to the bulk of produced small particles.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The levels of both nanoparticles (average size in general between 50 and 100 nm, as measured using the Nanotracer) and slightly larger particles (0.3 μm measured using the Lighthouse) were constantly much higher in the welding facility compared with the AM facility. High levels of nanoparticles in welding facilities are in line with what we found in the pilot study [7] and what is known from recent studies focusing on welding [15]. This may depend on the fact that in the welding facility, there are a wide array of different processes including welding, metal cutting, and combustion engines that may contribute to the bulk of produced small particles.…”
Section: Discussionsupporting
confidence: 89%
“…However, the levels of 10-μm particles in the AM facility must not be neglected because these particles could still be harmful if inhaled or ingested. Inhalation of metal particles alters nasal lavage fluid acute-phase proteins [15] and may increase cancer risk in the lungs, kidneys, and bladder [18].…”
Section: Discussionmentioning
confidence: 99%
“…WAP four-disulfide core domain protein 2 (Wfdc2) is an endopeptidase inhibitor known to be expressed in the respiratory tract. An earlier study of NLF from welders showed a decrease of Wfdc2 after controlled chamber exposure to welding fumes [ 19 ], similar to what we found in AM operators during year 1. Like Jchain, Wfdc2 was shown to be decreased in the nasal mucosa of individuals with allergic rhinitis as compared to healthy controls [ 25 ].…”
Section: Discussionsupporting
confidence: 88%
“…NLF constitutes an interesting matrix to identify early markers of exposure in the upper airways that could precede health effects. As such, it has previously been used in chamber studies of welding fumes [ 19 ] but is entirely novel for the much less studied AM environment. In this pilot study, the protein levels in NLF were investigated in AM operators and welders at two time points during a single workweek over two consecutive years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation